The construction and validation of a new scale for measuring features of constructivist learning environments in higher education - Alt, Dorit (Frontline Learning Research, 2014)
This study was aimed at mapping features of constructivist activities in higher education settings, constructing and validating a new scale for measuring their presence in lecture face-to-face based environments (LBE), seminars (SM), and distance learning environments (DLE). A mix-method approach was implemented in three phases. The first phase was aimed at qualitatively analysing classroom observational activities as experienced by students, in order to learn about actual instantiations of the theoretical constructivist features. The results foregrounded eight categories: ’knowledge construction’, ’authenticity’, ’multiple perspectives’, ’prior knowledge’, ’in-depth learning’, ’teacher- student interaction’, ’social interaction’ and ’cooperative dialogue’. The second phase was aimed at developing a questionnaire, based on the descriptions gathered in Phase 1. The third quantitative phase was used to validate the developed questionnaire (Constructivist Learning in Higher Education Settings scale [CLHES]) by using structural equation modelling. In addition, students’ academic self-efficacy had been chosen as a criterion variable in order to further assess construct validity of the CLHES. Lastly, a multivariate analysis of covariance was applied to allow the characterisation of differences between the learning settings in regard to the CLHES eight factors and academic self-efficacy. The scales were submitted to 597 undergraduate third-year college students. According to the main results: construct validity of the new scale has been confirmed; teacher-student and student-student interactions were positively connected to self-efficacy for learning; and SM were perceived as generally more constructivist when compared with the other learning environments. Implications of these findings and directions for future research are discussed.